1983
DOI: 10.1111/j.1440-1681.1983.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Permeability in Normal and Hypertensive Human Pregnancy

Abstract: Capillary permeability (CP) is elevated in late normal pregnancy, when compared to postpartum values. In women with pregnancy associated hypertension (PAH), pregnancy CP levels are not different from postpartum and are less than in normal pregnancy. These changes in capillary permeability are not explained by alterations in serum albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…The plasma volume on the low salt diet did not differ from that on the normal salt intake, but plasma volume expansion was observed on the high salt diet. There was no change in capillary permeability on any of the diets, although all pregnancy values were higher than postpartum measurements, confirming previous work (Hunyor et a/. 1983).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The plasma volume on the low salt diet did not differ from that on the normal salt intake, but plasma volume expansion was observed on the high salt diet. There was no change in capillary permeability on any of the diets, although all pregnancy values were higher than postpartum measurements, confirming previous work (Hunyor et a/. 1983).…”
Section: Resultssupporting
confidence: 89%
“…Capillary permeability was measured at the end of each diet by venous occlusion plethysmography as previously described (Hunyor et a/. 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been reported that capillary filtration is smaller in women with preeclampsia than in women with normal pregnancy, 2425 the difference of capillary filtration is small between nonpregnant women, women with normal pregnancy, and women with preeclampsia compared with the value of venous distensibility. 24 - 25 Thus, the decreased venous distensibility in women with preeclampsia was not likely due to the difference in capillary filtration.…”
Section: Methodological Considerationsmentioning
confidence: 99%